PEMBUATAN SENYAWA EPOKSI MINYAK SAWIT MENTAH (CPO) PADA TINGKAT KONSENTRASI PELARUT DAN WAKTU REAKSI BERBEDA (Production of Epoxy Compounds from CPO Performed at Different Concentrations and Reaction Time) - Alamsyah, Rizal (Jurnal Hasil Penelitian Industri, 2013)
One of the best ways to increase the added value of the CPO is to process itinto products such as epoxy. Epoxy is a commercial product that can be applied for severalpurposes such as plasticizer, stabilizer and coatings agents for polymeric resin. Theexperiments were conducted by reacting CPO (Crude Palm Oil) with benzene as a solvent,amberlite resin IR-120 as a catalyst, formic acid, and H2O2. The concentrations of thesolvent benzene were 15%, 25%, and 35% and the epoxidation reaction time were 2, 4, 6,and 8 hours. The results showed that the optimum reaction time was 6 hours and theconcentration of benzene used was 25%. Iodine number obtained was 1.84 g iod/100grCPO and oxirane oxygen content was 6.20%. The production of epoxy increased with thedecrease of iodine number.